Low-redshift quasars in the SDSS Stripe 82 – II. Associated companion galaxies and signature of star formation. Issue 1 (17th November 2020) - Stone, M B; Bettoni, D; Falomo, R; Kotilainen, J K; Karhunen, K; Paiano, S; Scarpa, R
ABSTRACT: We present optical spectroscopy of the close companions of 22 low-redshift ( z < 0.5) quasars (QSO) selected from a larger sample of QSO in the SDSS Stripe82 region for which both the host galaxy and the large-scale environments have been investigated in our previous work. The new observations extend the number of QSO studied in our previous paper on close companion galaxies of 12 quasars. Our analysis here covers all 34 quasars from both this work and the previously published paper. We find that half of them (15 QSO; ∼44 per cent) have at least one associated galaxy. Many (12 galaxies; ∼67 per cent) of the associated companions exhibit [O ii ] 3727 Å emission line as signature of recent star formation. The star formation rate (SFR) of these galaxies is modest (median SFR ∼ 4.3 M⊙ yr −1 ). For eight QSO, we are also able to detect the starlight of the host galaxy from which three have a typical spectrum of a post-starburst galaxy. Our results suggest that quasars do not have a strong influence on the star formation of their companion galaxies.